Trans-(3S, 4S)-Disubstituted pyrrolidines as inhibitors of the human aspartyl protease renin. Part I: Prime site exploration using an amino linker. Issue 8 (15th April 2015) - Lorthiois, Edwige; Cumin, Frederic; Ehrhardt, Claus; Kosaka, Takatoshi; Sellner, Holger; Ostermann, Nils; Francotte, Eric; Wagner, Trixie; Maibaum, Jürgen
Graphical abstract: Abstract: Recently, we reported on the discovery of (3 S, 4 S )-disubstituted pyrrolidines (e.g., 2 ) as inhibitors of the human aspartyl protease renin. In our effort to further expand the scope of this novel class of direct renin inhibitors, a new sub-series was designed in which the prime site substituents are linked to the pyrrolidine core by a (3 S )-amino functional group. In particular, analogs bearing the corresponding sulfonamide spacer (50, 51 and54a ) demonstrated a pronounced increase in in vitro potency compared to compound2 .